2021
DOI: 10.1111/nuf.12610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of assertiveness training on the nursing students' assertiveness and self‐esteem levels: Application of hybrid education in COVID‐19 pandemic

Abstract: The changes taking place in the education system along with the coronavirus disease 2019 pandemic make it compulsory to use distance education methods. For evaluating whether the assertiveness training which was offered through a hybrid education model had any effect on assertiveness and self‐esteem, this study was conducted as an experimental study with the control group. In the study, the Rathus assertiveness inventory, Coopersmith self‐esteem inventory, and personal information form were utilized. The parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
(45 reference statements)
0
5
1
Order By: Relevance
“…Our results contribute to the ongoing discussion about the intersection of culture and education. Recognizing cultural influences on assertive behaviors within the academic context should prompt further research in cross-cultural educational psychology (Ayhan & Seki, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our results contribute to the ongoing discussion about the intersection of culture and education. Recognizing cultural influences on assertive behaviors within the academic context should prompt further research in cross-cultural educational psychology (Ayhan & Seki, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recognition of gender differences among surgical trainees, a knowledge gap remains surrounding potential interventions to reduce these discrepancies. Although interventions have been evaluated among nonsurgical populations, such as benefits of assertiveness workshops among nursing and high-school students and one study among medical students, 24 - 26 the effects among surgeons and other medical professions are still largely unknown. Given that multiple previous studies have shown that female surgeons experience higher degrees of burnout compared with their male counterparts, 27 28 29 30 it is imperative this gender gap is addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Assertiveness is considered an essential requirement for effective nurse/patient communication, and having such skills improves the confidence of nursing professionals (Yurtsal & Özdemir, 2015). Inculcating assertiveness among nursing students, is important in producing confident nurses for the future, who would defend their rights as well as their patients (Ayhan & Seki, 2021). However, nursing students begin to encounter problems in clinical setting after commencing their clinical education causing a decrease in their assertiveness levels (Ünal, 2012).…”
Section: Advantages Of Assertiveness For the Nursing Professionmentioning
confidence: 99%